Bilingual and Monolingual Infants' Recognition of Words Spoken in Foreign Accents - Dillon, Brendan R. (Tufts Archival Research Center, 2005)
Lexical acquisition is one of the most challenging tasks human infants face. Once they are able to separate and identify word forms from fluent speech and map those words onto their meanings, infants must also decipher how much perceptual change in speech is indicative of a phonetic and thus potential meaning change. The current study investigated the effect of foreign accents on recognition of familiar words in bilingual and monolingual 16 to 24-month-olds. Infants were presented with a pair of visual stimuli and asked to find one of them by a word spoken in either a familiar American English accent or a foreign Mandarin Chinese or Mexican Spanish accent. Successful performance on the task was indicated by a significantly greater persistence to the target picture if initially fixated when the word was said in comparison to persistence to the nontarget picture if initially fixated when the word was said. Within the monolingual group, infants displayed a strong understanding of the target words spoken in all three of the tested accents. Exposure to a foreign accent did not provide any additional benefit to later recognition of words spoken in that accent. Furthermore, age and word production both affected performance on the task, such that both older and more advanced talkers displayed stronger performance. Finally, bilingual infants also demonstrated a clear understanding of the target words, as measured through the persistence difference to the target versus nontarget pictures. As in the monolingual group, the bilingual infants understood all three accents equally well. However, there was some suggestion that the bilinguals showed weaker performance on the task overall. In summary, the early word learning infants in this study demonstrated the remarkable ability to understand words spoken in both familiar and foreign accents, even without previous exposure.